2021
DOI: 10.1186/s40494-021-00622-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide snow cleaning of paper

Abstract: The cleaning of particles from smooth and rough paper surfaces using a high-speed CO2 snow jet was investigated. The measurements included characterization of the jet properties, determination of the cleaning efficiency, and evaluation of any possible adverse effects. The method was compared with nitrogen jet cleaning and dry cleaning by commercial materials. The results showed that the CO2 snow jet is able to effectively remove particles from the paper surface and did not cause any observable degradation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The instrument can generate also a N2 jet (without CO2 flow). The properties of the CO2 snow spray generator are characterised in the previous study (Mašková et al 2021). The samples were automatically treated by the CO2 snow jet using the newly developed cleaning system (see Fig.…”
Section: Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument can generate also a N2 jet (without CO2 flow). The properties of the CO2 snow spray generator are characterised in the previous study (Mašková et al 2021). The samples were automatically treated by the CO2 snow jet using the newly developed cleaning system (see Fig.…”
Section: Cleaningmentioning
confidence: 99%
“…Dry ice pellet blasting has been used for the restoration of books exposed to smoke (Silverman 2009;Silverman and Irwin 2009) or metallic objects (van der Molen et al 2010;Cutulle and Kim 2015). In a pilot study (Mašková et al, 2021), we investigated N2 jet and CO2 snow jet cleaning of paper using a manually guided nozzle. The results indicated that the CO2 snow jet is a promising method for cleaning of cellulose-based library materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it ensures the safety of the surfaces by avoiding abrasion due to the low hardness of the pellets used (2 Mohs) [46] and favours the reduction in air pressure required compared to other mechanical methods [47]. It is a versatile cleaning method, due to its ability to adapt to different parameters and delicate surfaces [48] and unique treatment, as it does not leave residues on the treated surface that would require a second washing or drying of the surface [49]. On the other hand, a comparative study with other types of spraying methods such as sand blasting or water blasting, carried out by researchers from the Department of Civil, Architectural, and Environmental Engineering of the University of Miami, found that it required 19% less energy than other techniques, in addition to reducing the average time of use by 77%, validating it as an efficient and safe technique for its application to architectural structures [50].…”
mentioning
confidence: 99%